A preferred orientation correction to describe a fiber texture under glancing incidence. (18th January 2013) - Simeone, David; Gosset, Dominique; Baldinozzi, Gianguido
<x xml:space="preserve">Abstract</x> Much work is nowadays being devoted to the characterization of the structure and the microstructure of thin films and mesoporous materials. Different physical and chemical processes used to elaborate these thin films often induce a fiber texture in these materials. The X‐ray glancing‐incidence technique appears to be a useful tool for collecting diffraction patterns of thin films while avoiding the peaks of the substrate. However, the scattering vector in this asymmetric scattering geometry is not perpendicular to the surface of the sample. This point implies that the correction developed to model the effects of a fiber texture in Bragg–Brentano geometry, where the scattering vector is always normal to the surface of the sample, cannot be applied in glancing incidence. This work presents a procedure to correct the preferred orientation due to this fiber texture in asymmetric scattering geometry and then in glancing incidence. By an example, it is proved that this correction of the fiber texture is efficient. The main point of interest regarding this correction is that only a few parameters are needed to handle the effect of the fiber texture on the diffraction patterns collected in asymmetric scattering geometry and then under glancing incidence.